Mary Carty - Carty, Mary (Irish Journal of Arts Management and Cultural Policy, 2015)
Mary Carty, entrepreneur and author, observed how our thinking about cultural products and practices can become siloed. The solution is to invest in and develop our capacity for collaborative practice, cutting cuts across artificial divisions between the arts and the cultural industries. Thank you all for having me here today, it’s an honour to be here. There are two points I want to talk about that struck me from listening to all the conversations today. The first one is, where do we put cultural products and what are they? The second one is about collaboration. We’ve talked so much about collaboration today and I have a few ideas around that that I’d like to share.